Factors Related Pain Catastrophizing in Hospitalized Patients with Trauma - Nantawong, Prampree; Tankumpuan, Thitipong; Utriyaprasit, Ketsarin; Owattanapanich, Natthida (Siriraj Medical Journal, 2023)
Objective: This study aimed to explore the factors related to pain catastrophizing (PC) in hospitalized patients with trauma within 72 hours of injury. Materials and Methods: The study was a cross-sectional correlation study. The sample was 109 patients who were admitted to ICU Trauma or General Trauma Unit within 72 hours after injury and were aged 18 years and over. They were diagnosed with at least one or multiple organs of injury with a Glasgow Coma Scale (GCS) between 13 and 15. Pearson’s product-moment correlation coefficient, spearman rank correlation, point-biserial correlation, and linear multiple regression were used to analyze the data. Results: The results showed that more than half of the sample was male (73.0%) with the age range from 18 to 91 years. During admission, the subjects complained about pain at moderate to severe levels (68.5%). The prevalence of PC was 11.9%. A few participants (2.8%) experienced anxiety. Also, more than half of them (63.3%) had ADLs in independent to absolutely independent levels. Almost 50.5% of the participants experienced poor sleep quality. Lastly, 50.5% of them were in frailty and pre-frailty conditions. There was a positive relationship between PC and anxiety (r = .439, p < .01). Finally, anxiety could explain the variance of PC by 19.3% (F1,107 = 25.571, P < .001). Conclusion: Based on the study findings, the predictor of PC was anxiety. Thus, healthcare providers should assess this factor, in order to provide interventions to reduce high levels of anxiety leading to the prevention of PC occurrences in hospitalized trauma within 72 hours after injury.